ILP-MODEL AND LP-MODEL OF THE NEURAL NETWORK LEARNING PROBLEM - Jovančevski, Gjorgji; Karčicka, Dimitra; Božinovski, Stevo (Matematichki Bilten, 1998)
It has been shown that the problem of Neural Network Pattern Recognition Learning can be considered as an Integer Linear Programming (ILP) problem and as an Linear Programming (LP) problem.